Stanowisko parczeliny trójlistkowej Ptelea trifoliata L. ssp. trifoliata w lasach Nadleśnictwa Wyszków - Ciosek, Marek; Krechowski, Janusz; Piórek, Katarzyna; Sikorski, Roman (Leśne Prace Badawcze, 2016)
This paper presents the results of studies carried out on Ptelea trifoliata populations in the Wyszków Forest District in 1998 and 2013. Ptelea trifoliata is a native species of North America (United States of America, northern part of Canada) and has a wide ecological range. However, it prefers fertile, wet soils and moderate light. In Europe it is planted for its decorative value and is mainly found in synanthropic habitats (parks, graveyards, roadsides, fortifications) in Poland. The station of Ptelea trifoliata is situated in the oak-hornbeam forest, Tilio-Carpinetum typicum , with a significant fraction of the stand consisting of Pinus sylvestis . Hop trees occur mainly along forest section lines and are rarely found inside the sections. In the last 15 years an increase in the number and size of Ptelea trifoliata clusters has been observed. The species spreads along forest section lines, which form a convenient migration route by creating favourable conditions for the germination and growth of seedlings (good access to light, fragments of bare soil). The presence of new individuals far from the pre-existing clusters indicates that the generative way of propagation dominates. Biometric measures indicate significant differences in length and width of whole leaves as well as leaflets, with leaves and leaflets of vegetative specimens significantly larger than generative ones. As a consequence of the high rate of Ptelea trifoliata expansion along forest section lines and occurrence of single specimens inside the forest sections, we assume this species to be potentially invasive.